(untitled) (Palíndromo, 2020)
This paper aims to present an experience report of a workshop held at CREAS - Specialized Reference Center for Social Assistance, a non-formal teaching space in the city of Rio Grande, RS, as its pedagogical artistic proposal the study of hip-hop culture and the concept of relational aesthetics. It is a biographical work that analyzes my career as an artist and reflects on art concepts found in hip-hop productions added to my work as a workshop artist. We used authors such as Nicolas Bourriaud (1998) who dialogues directly with the concepts of relational aesthetics in addressing the trajectory of an artist engaged in the hip-hop cultural movement and how he recognizes himself from his own production. It also analyzes the existence of the aesthetic experience contained in hip-hop workshops, which makes the other also create relationships with this culture.